Essential Oil from Pinus Koraiensis Pinecones Inhibits Gastric Cancer Cells via the HIPPO/YAP Signaling Pathway - Zhang, Yandong (Molecules, 2019)
Pinecone is a traditional folk herb, which has been used in China for many years. In this paper, the essential oil from Pinus koraiensis pinecones (PEO) was obtained by hydrodistillation and 41 compounds were identified by gas chromatography–mass spectrometry (GC-MS), mainly including α-Pinene (40.91%), Limonene (24.82%), and β-Pinene (7.04%). The purpose of this study was to investigate the anti-tumor activity of PEO on MGC-803 cells and its mechanism. Anti-tumor experiments in vitro showed PEO could significantly inhibit the proliferation and migration of MGC-803 cells, and it also could arrest the cell cycle in the G2/M phase, decrease the mitochondrial membrane potential, and induce apoptosis. Finally, the effects of PEO on genes expression on MGC-803 cells were analyzed by RNA sequencing, and results showed that after treatment with PEO, 100 genes were up-regulated, and 57 genes were down-regulated. According to the KEGG pathway and GSEA, FAT4, STK3, LATS2, YAP1, and AJUBA were down-regulated, which were related to HIPPO signaling pathway. Real-time PCR and western blot further confirmed the results of RNA sequencing. These results indicated that PEO may exert anti-tumor activity via the HIPPO/YAP signaling pathway. The anti-tumor mechanism of this oil can be further studied, which is important for the development of anti-tumor drugs.